2011
DOI: 10.1002/pat.1760
|View full text |Cite
|
Sign up to set email alerts
|

A method for simultaneously improving the flame retardancy and toughness of PLA

Abstract: In order to modify the brittleness and flame retardant properties of poly(lactic acid) (PLA), a series of flame retardant toughened PLA composites were prepared using poly(ethylene glycol) 6000 (PEG6000) as a toughening and charring agent together with ammonium polyphosphate (APP) as an acid source and blowing agent. The fire and thermal behavior of PLA/PEG/APP composites was evaluated by limiting oxygen index (LOI), UL‐94, cone calorimeter, and thermogravimetric analysis (TGA). The results showed that the PLA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(98 citation statements)
references
References 27 publications
2
92
1
3
Order By: Relevance
“…Moreover, the residue in the case of UMC was negligible. Therefore, these results are in agreement with those that have been previously reported [67]. In addition, the chemical linkage between PEG, PLA and magnetite could be confirmed by the FTIR spectra of Ugi magnetite composite ( Figure 11).…”
Section: Synthesis Of Ugi Magnetic Compositesupporting
confidence: 92%
“…Moreover, the residue in the case of UMC was negligible. Therefore, these results are in agreement with those that have been previously reported [67]. In addition, the chemical linkage between PEG, PLA and magnetite could be confirmed by the FTIR spectra of Ugi magnetite composite ( Figure 11).…”
Section: Synthesis Of Ugi Magnetic Compositesupporting
confidence: 92%
“…APP has been also combined with a simple poly(ethylene glycol) [285]. Efficient alternative to APP turned out to be AlPi coupled with nanoparticles having a different aspect ratio [168], PEPA derivatives [286], PEPA coupled with POSS [165] or aryl polyphosphates [287].…”
Section: Poly(butylene Succinate) and Poly(lactic Acid)mentioning
confidence: 98%
“…Wang et al found that the incorporation of an intumescent flame retardant and ZnAl-LDH was very efficient in improving the flame retardance of PLA composite [3]. In our recent studies, we report a series of flame retardant toughened PLA composites that have been prepared using poly(ethylene glycol) (PEG6000) and ammonium polyphosphate (APP) [4]. In the meantime, a novel method of synthesis of phosphorus-containing poly(lactic acid) to improve the flame retardance of PLA has been developed in our latest work [5].…”
Section: Introductionmentioning
confidence: 95%